Papillary carcinoma thyroid serving as recipient tumor to carcinoma breast: A rare example of tumor-to-tumor metastasis - Anila Kunjulekshmyamma Raveendrannair; Anitha Mathews; Bipin T Varghese; K Jayasree (Wolters Kluwer Medknow Publications, 2019)
A 36-year-old female presented with lump in the left breast of 2 months duration. Fine-needle aspiration cytology (FNAC) and trucut biopsy confirmed the diagnosis of carcinoma. Clinically, it was T3N1Mx disease. Computed tomography (CT) of the chest detected bilateral lung metastasis. CT head and neck detected a nodule in the thyroid which on FNAC was suspicious of papillary carcinoma. The patient was started on chemotherapy for breast disease with a good initial response; however, while on-follow up, there was progression of disease at primary site. The patient was taken up for surgery. Radical mastectomy along with total thyroidectomy was performed. Histopathological examination showed infiltrating duct carcinoma, not otherwise specified type and papillary carcinoma thyroid. There was a 0.4 cm × 0.4 cm metastatic focus, from breast carcinoma within the papillary carcinoma thyroid. The metastasis was confirmed by immunohistochemistry. Metastasis to thyroid is rare. However, tumor-to-tumor metastasis with papillary carcinoma serving as recipient to breast carcinoma is exceedingly rare with very few case reports in the literature. We report this case for its rarity and also for highlighting the fact that pathologists should keep in mind the possibility of metastasis also when coming across unusual morphology in thyroid lesions.